Making markets work for forest communities - Scherr, Sara J.; White, A.; Kaimowitz, D. (Forest Trends and CIFOR, 2002)
This policy brief lays out strategies to improve the contribution of forest markets to local livelihoods. It is offered as a first step in a longer-term effort to promote forest markets that enhance the livelihoods of poor people while conserving forest resources. While forests are providing critical safety nets and subsistence for the poor there are specific niches where large numbers of low-income producers have-or could develop-competitive advantage.It is vital to alter the policies that hinder forest producers' income opportunities, and to engage the private sector in forging successful community business partnerships.